Factors Affecting Commitment Organization at the Provision Implementation Center Sulawesi Housing I - Karmila Monoarfa; Djamila Podungge; Maman Musa (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine the factors that influence organizational commitment at the Sulawesi I Housing Provision Agency. This type of research is descriptive research with a quantitative approach. The type of data used is primary data and secondary data with data sourced from observations, questionnaires and documentation. The population in this study amounted to 26 people who are substantive employees totaling 17 people and civil servants 9 people. The results of this test are hypothesized to be able to test the factors that influence organizational commitment at the Sulawesi I Housing Implementation Center. It has been tested that the level of organizational commitment can be influenced by personal factors. The influence of personal factors is 93.85%. The results of this study indicate that in general it confirms the hypothesis that has been stated previously that the existence of personal factors affects organizational commitment.